Reducing Regional Poverty Rate in Central Java - Sriyana, Jaka (Universitas Negeri Semarang, 2018)
This paper elaborates some appropriate policies regarding regional poverty reduction in Central Java province. This research estimates a poverty model based on a set of panel data comprising 29 regencies and six cities from 2011 to 2016. A fixed-effect model presents that poverty rate has a negative association with regional economic growth, minimum wage level, number of unemployment, and the quality of human resources. The higher number of population significantly decreases poverty rate in each region. Also, this study indicates that there is more poverty rate in the eastern region than that in the west region.Ã‚Â Moreover, the percentage of the poverty rate in regencies remains higher than the level in the cities. Overall, these results indicate that the local governments have successfully managed the poverty issues in among regencies and cities. This research finds that local governments are on the right way in their public policies in the development process. For more effective in poverty reduction, the local governments in the eastern region have to improve their human resources quality.